The Effect of Kangaroo Mother Care on Increasing the Body Weight in Infants with Low Birth Weight: A Meta-Analysis - Handayani, Anggun Fitri; Dewi, Yulia Lanti Retno; Pamungkasari, Eti Poncorini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Low Birth Weight (LBW) is a condition of babies born weighing <2,500 grams regardless of gestational age. Stabilization of the general condition is an important thing to do during the treatment period, there are several treatments for LBW babies, namely standard care with an incubator, monitoring nutritional intake and doing kangaroo mother care. This study aims to analyze the effect of kangaroo mother care on weight gain in LBW infants, with a meta-analysis of primary studies conducted by previous authors. Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: infants with low birth weight. Intervention: Kangaroo Mother Care. Comparison: Conventional Method Care. Outcome: weight gain. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, Science Direct and Springerlink. Keywords to search for articles “kangaroo mother care” AND “weight gain” OR “growth” AND “neonatal outcome” AND “low baby weight infants” OR “skin to skin contact” OR “kangaroo care” OR “kangaroo method” AND “Randomized Controlled Trial” OR “RCT”. The articles included are full-text English and Indonesian with a study design of a Randomized Controlled Trial from 2007 to 2020 and reporting on the Mean and SD in multivariate analysis. The selection of articles is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application. Results: A total of 11 randomized controlled trials from India, Nepal, Pakistan, Bangladesh, Malaysia, Kenya, and Egypt were selected for a systematic review and meta-analysis. The data collected showed that kangaroo mother care increased the weight of LBW infants and was statistically significant (SMD= 1.05; 95% CI= 0.56 to 1.54; p<0.001). Conclusion: Kangaroo mother care increases weight in LBW babies.